Hydraulic modeling of a compact stormwater treatment device applying concepts of dynamic similitude. (1st February 2023) - Stricker, Max; Littfinski, Tobias; Pecher, Klaus Hans; Lübken, Manfred; Wichern, Marc
Abstract: The development of compact treatment devices (CTDs) with high removal efficiencies and low space requirements is a key objective of urban stormwater treatment. Thus, many devices utilize a combination of sedimentation and upward-flow filtration in a single system. Here, sedimentation is used before filtration, which makes it difficult to evaluate the individual treatment stages separately. This study determines the removal efficiency by sedimentation and the expected filter load in a specific compact treatment device designed for a catchment area of up to 10, 000 m 2 . In contrast to a full-scale investigation, small-scale physical hydraulic modeling is applied as a new cost-saving alternative. To validate upscaling laws, tracer signals and particle-size-specific removal efficiencies are determined for two geometrically similar models at different length scales. Thereby, Reynolds number similarity produces similar flow patterns, while the similarity of Hazen numbers allows to upscale removal efficiencies. Upscaling to the full-scale reveals that the filter in the device is only partly loaded by particulate matter that consists mostly of particles ≤63 μm. Thus, sedimentation upstream of a filter is of relevant importance in CTDs. The proposed dimensionless relationship may be used for particles from different catchments and helps to size the device accordingly. HIGHLIGHTS: A small-scale approach is presented to study the gravity-driven removal efficiency in a compact stormwater treatment device that combines sedimentation and filtration. The Hazen number is successfully applied to scale the gravity-driven removal of particles from a small- to a full-scale model. The filter stage of the device is only partially loaded with particulate matter, which mostly consists of particles ≤63 μm. Graphical Abstract